Pseudogenization of the cntQ permease confers distinct yersinopine-metal uptake selectivity in Yersinia species - Clémentine Laffont; Elizabeth Pradel; Laurent Ouerdane; Amélie Dewitte; Nicolas Oswaldo Gomez; Mathilde Tribout; Catherine Brutesco; Romé Voulhoux; Ryszard Lobinski; Florent Sebbane; Pascal Arnoux (BioMetals, 2026)
Yersinopine, a nicotianamine-like metallophore, was recently identified through biochemical analyses, but its in vivo production and functional role remain uncharacterized. In Yersinia pseudotuberculosis and its recent descendant Yersinia pestis , the cnt operon ( cntPQRLMI ) putatively encodes the biosynthesis and transport of yersinopine. In Y. pestis , however, two frameshift mutations disrupt cntQ , which encodes the predicted permease for yersinopine-metal complexes. This pseudogenization raises critical questions about the functional relevance of yersinopine in these closely related species. Here, we show that cnt operon expression is repressed by the zinc uptake regulator Zur and that both Y. pestis and Y. pseudotuberculosis secrete yersinopine under zinc-limited conditions. Unexpectedly, the operon mediates iron uptake in Y. pseudotuberculosis but supports zinc acquisition in Y. pestis . Moreover, targeted disruption of cntQ in Y. pseudotuberculosis shifts metal specificity from iron to zinc, mimicking the Y. pestis phenotype. Collectively, our results suggest that a single pseudogenization event could rewire metal uptake specificity. Our findings illustrate how evolutionary genome reduction can reshape bacterial physiology.

Structural and textural analysis of the precursor of Laponite synthesis: Enhanced hydrogen adsorption in a clay material - Mohammad AbdelSater; Martine Lanson; Valérie Magnin; Erwan Paineau; Cristina Coelho; Delphine Vantelon; Erik Elkaim; Jean-Pascal Rueff; Victor Balédent; Marie-Vanessa Coulet; Virginie Marry; Lorella Masci; et al. (Applied Clay Science, 2026)

Vancomycin-resistant Enterococcus faecium: a national wide genomic snapshot in Switzerland - Dominique S. Blanc; Florian Mauffrey; Andrea C. Büchler; Danielle Vuichard-Gysin; Vanja Piezzi; Céline Gardiol; Marc Garcia; Trestan Pillonel; Laurent Poirel; Patrice Nordmann; Pascal Schlaepfer; Claudio Neidhöfer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Self-assemblies from prodrugs composed of antimicrobial peptides: a revolution in local lung cancer treatment, with microbiota as a main actor - Abdallah Ladaycia; Laurent Lemaire; Hélène Pailhoriès; Nolwenn Lautram; Florence Franconi; Pascal Pigeon; Gérard Jaouen; Catherine Passirani; Elise Lepeltier (Drug Delivery and Translational Research, 2026)

Impacts of long-term cassava-based conservation agriculture systems on soil greenhouse gas emissions in Cambodia - Vira Leng; Laurent Thuriès; Vang Seng; Florent Tivet; Phearum Mark; Chhay Ngin; Try Yorn; Titouan Filloux; Pascal Lienhard; Johan Six; Lyda Hok; Stéphane Boulakia; et al. (Agriculture, Ecosystems & Environment, 2026)

Interception of copper fungicides by cover crops as a way to prevent soil contamination in vineyards? - Jean-Yves Cornu; Claire Lasserre; Jean-Marc Deogratias; Jean-Pascal Goutouly; Laurent Delière; Diana Salvador; Sónia M. Rodrigues; Astrid Avellan (Journal of Environmental Management, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Floristic diversity of the lower stratum of smallholder’s palm oil plantations around Yaoundé in Cameroon - Laurent Florent Menyene Etoundi; Roméo Pascal Ngah; Jules Christian Zekeng; Joseph Achille Messi Effa; Elvis Mouyakan A. Moumbock; Ecclésiaste Marien Ambombo Onguene; Pierre Marie Chimi; Gislain Mofack; Paul Patrick Endele; Léon Dieudonné Kono; André Paul Ebanga; Danielle Bertille Osso; et al. (Agroforestry Systems, 2025)

Healthy soils as a booster to EU competitiveness - Panos Panagos; Alberto Orgiazzi; Emanuele Lugato; Guillaume Vandenesch; Laurent Thannberger; Jason C. Neff; Arjan Reijneveld; Erik Mathijs; Pascal Chapot; Sara Guerrini; Darina Štyriaková; Julian Kremers; et al. (Land Use Policy, 2025)

Coupling 2D hydro-sedimentary modelling with tracer-based flow competence estimation to determine critical bed shear stress - Guillaume Piasny; Pierre-André Garambois; Pascal Finaud-Guyot; Laurent Schmitt (Geomorphology, 2025)

LC-MS analysis-based molecular networking for identifying anthelmintic compounds in Terminalia leiocarpa, a traditional plant used in livestock farming in West Africa - Esaïe Tchetan; Sergio Ortiz; Pascal Abiodoun Olounladé; Kristelle Hughes; Patrick Laurent; Erick Virgile Bertrand Azando; Sylvie Mawule Hounzangbe-Adoté; Fernand Ahokanou Gbaguidi; Joëlle Quetin-Leclercq (Phytochemistry Letters, 2025)

High-resolution building stock energy model for assessing the impact on the load curve of residential space heating electrification - Valentin Moreau; Marie-Hélène Laurent; Thomas Berthou; Bruno Duplessis; Pascal Stabat (Energy and Buildings, 2025)

Building resilient urban water systems: emerging opportunities for solving long-lasting challenges - Bertil Nlend; Andrea Reimuth; Liang Emlyn Yang; Mahesh Jampani; Elena Cristiano; Benjamin Dewals; Elizabeth Boyer; Irem Daloglu Cetinkaya; Laurent Pascal Diémé; Ratnadeep Dutta; Wenhan Feng; Giovanna Grossi; et al. (Hydrological Sciences Journal, 2025)

Adhesion of cool roof coatings to mudbrick and corrugated metal roofs: manual peel adhesion testing - Aditi Bunker; Guillaume Compoaré; Susan T Jackson; Denia Kolokotsa; Sandra Barteit; Martina Anna Maggioni; Jose Guillermo Cedeno Laurent; Jonathan J Buonocore; Siaka Debe; Simiao Chen; Prasad Liyanage; Pippa McKelvie-Sebileau; et al. (Next Research, 2025)

Correction to: Outpatient parenteral antibiotic therapy in non-cystic fibrosis lung transplant recipients: characteristics, efficacy and safety - Bart Forier; Veronique Schaevers; Isabel Spriet; Charlotte Quintens; Stefanie Desmet; Saskia Bos; Pascal Van Bleyenbergh; Natalie Lorent; Laurens De Sadeleer; Laurent Godinas; Lieven J. Dupont; Robin Vos (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Outpatient parenteral antibiotic therapy in non-cystic fibrosis lung transplant recipients: characteristics, efficacy and safety - Bart Forier; Veronique Schaevers; Isabel Spriet; Charlotte Quintens; Stefanie Desmet; Saskia Bos; Pascal Van Bleyenbergh; Natalie Lorent; Laurens De Sadeleer; Laurent Godinas; Lieven J. Dupont; Robin Vos (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Multiple layers of regulators emerge in the network controlling lateral root organogenesis - Antoine Beckers; Akihito Mamiya; Masahiko Furutani; Malcolm J. Bennett; Hidehiro Fukaki; Shinichiro Sawa; Pascal Gantet; Laurent Laplaze; Soazig Guyomarc’h (Trends in Plant Science, 2025)

MORPHEE a multiphysics tool for control rod withdrawal modeling in SFR - Marlène Jeannin; Laurent Buiron; Vincent Pascal (Annals of Nuclear Energy, 2024)

40Ar diffusion in phlogopite: P V T atomistic calibration and implications for Ar–melt–solid kinetic interactions and ascent dynamics of mantle xenoliths and kimberlites - Jehiel Nteme; Stéphane Scaillet; Pascal Brault; Laurent Tassan-Got; Florian Duval (Geochimica et Cosmochimica Acta, 2024)

Optimal species proportions, traits and sowing patterns for agroecological weed management in legume–cereal intercrops - Pierre Lebreton; Laurent Bedoussac; Catherine Bonnet; Etienne-Pascal Journet; Eric Justes; Nathalie Colbach (European Journal of Agronomy, 2024)

Lagrangian and Eulerian modelling of 106Ru atmospheric transport in 2017 over northern hemisphere - Léo Adenis; Sylvain Mailler; Laurent Menut; Pascal Achim; Sylvia Generoso (Journal of Environmental Radioactivity, 2024)

Sialic acids cleavage induced by elastin-derived peptides impairs the interaction between insulin and its receptor in adipocytes 3T3-L1 - Alexandre Guillot; Kevin Toussaint; Lucrece Ebersold; Hassan ElBtaouri; Emilie Thiebault; Tarik Issad; Franck Peiretti; Pascal Maurice; Hervé Sartelet; Amar Bennasroune; Laurent Martiny; Manuel Dauchez; et al. (Journal of Physiology and Biochemistry, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

X-ray tomography applied to tsunami deposits: Optimized image processing and quantitative analysis of particle size, particle shape, and sedimentary fabric in 3D - Saptarshee Mitra; Raphaël Paris; Laurent Bernard; Rémi Abbal; Pascal Charrier; Simon Falvard; Pedro Costa; César Andrade (Marine Geology, 2024)

Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

Ecological assessment of combined sewer overflow management practices through the analysis of benthic and hyporheic sediment bacterial assemblages from an intermittent stream - Adrien C.M. Pozzi; Stéphanie Petit; Laurence Marjolet; Benjamin Youenou; Mickaël Lagouy; Philippe Namour; Laurent Schmitt; Oldrich Navratil; Pascal Breil; Flora Branger; Benoit Cournoyer (Science of The Total Environment, 2024)

HPLC-LTQ orbitrap mass spectrometry-based molecular networking for identifying anthelmintic molecules in Morinda lucida Benth - Esaïe Tchetan; Sergio Ortiz; Kristelle Hughes; Pascal Abiodoun Olounladé; Patrick Laurent; Erick Virgile Bertrand Azando; Marie-France Herent; Sylvie Mawule Hounzangbe-Adote; Marcel Romuald Benjamin Houinato; Fernand Ahokanou Gbaguidi; Joëlle Quetin-Leclercq (South African Journal of Botany, 2023)

Precipitation patterns and N availability legacy govern microbial response to rewetting in a plant-soil system - Ilonka C. Engelhardt; Pascal A. Niklaus; Florian Bizouard; David Bru; Marie-Christine Breuil; Nadine Rouard; Arnaud Mounier; Laurent Philippot; Romain L. Barnard (Soil Biology and Biochemistry, 2023)

Dosimetry in the lungs of α-particles (210Po) and β-particles (210Pb) present in the tobacco smoke of conventional cigarettes and heated tobacco products - Laurent Desorgher; Aurélie Berthet; Jérémie Rossier; François Bochud; Pascal Froidevaux (Journal of Environmental Radioactivity, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

A systematic review of the views of healthcare professionals on the scope of preimplantation genetic testing - Maria Siermann; Zoë Claesen; Laurent Pasquier; Taneli Raivio; Olga Tšuiko; Joris Robert Vermeesch; Pascal Borry (Journal of Community Genetics, 2022)

Therapeutic failures of targeted antibiotic prophylaxis in urology - Elodie Curlier; Yvanne Sadreux; Samuel Markowicz; Laurent Brureau; Sunniva Donat; Pascal Blanchet; Pierre-Marie Roger (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

A network of water vapor Raman lidars for improving heavy precipitation forecasting in southern France: introducing the WaLiNeAs initiative - Cyrille Flamant; Patrick Chazette; Olivier Caumont; Paolo Di Girolamo; Andreas Behrendt; Michaël Sicard; Julien Totems; Diego Lange; Nadia Fourrié; Pierre Brousseau; Clotilde Augros; Alexandre Baron; et al. (Bulletin of Atmospheric Science and Technology, 2021)

Commensal small mammal trapping data in Southern Senegal, 2012–2015: where invasive species meet native ones - Laurent Granjon; Odile Fossati‐Gaschignard; Emmanuelle Artige; Khalilou Bâ; Carine Brouat; Ambroise Dalecky; Christophe Diagne; Mamoudou Diallo; Philippe Gauthier; Pascal Handschumacher; Mamadou Kane; Lætitia Husse; et al. (Ecology, 2021)
Describing patterns and testing hypotheses on processes driving biological invasions represent major issues in ecology. Addressing these questions requires building adequate data sets, i.e., covering areas and spanning periods adapted to the invasion processes studied. Rodents include major invasive species, among which the black rat Rattus rattus and the domestic mouse Mus musculus have nearly colonized the entire world, from their native Asian range. To do so, they have benefitted from their ability to cope with human‐modified environments and to live in the immediate vicinity of Man, who served as a vector of their dispersal between regions and continents. In Senegal, both R . rattus and M . musculus , initially introduced by early West European colonizers some centuries ago, are currently expanding thanks to road traffic and infrastructure development and rampant urbanization that concerns even remote regions of the country. As part of projects aimed at studying (1) the role of invasive black rat populations in the emergence of zoonotic diseases in southeastern Senegal, and (2) the evolutionary consequences of parasites in R . rattus and M . musculus invasions in Senegal, we conducted a series of field campaigns throughout the southern half of the country, between May 2012 and September 2015. The objectives were to catch commensal small mammals using standard trapping procedures, identify them using morphological or molecular tools, and take samples from them upon autopsy, to look for zoonotic parasites and pathogens. Along with data on individual specimens, information on microhabitats was gathered at each trap position. This resulted in the constitution of a data set of more than 13,000 trapnights, which allowed the capture of more than 3,100 small mammals, all characterized by a series of associated biological, geographical, and environmental data. The small mammals concerned are mainly rodents (10 species), shrews, and hedgehogs. The two invasive rodent species were the most numerous, exceeding in numbers all the other species pooled. This data set makes it possible to study coarse to fine‐scaled distribution of species of this commensal community in southern Senegal, as well as the possible determinants of this distribution in terms of habitat preferences and/or interspecific interactions. This data set can be freely used for non‐commercial purposes and is licensed under a Creative Commons Attribution 4.0 International License.

Precipitation patterns and N availability alter plant-soil microbial C and N dynamics - Ilonka C. Engelhardt; Pascal A. Niklaus; Florian Bizouard; Marie-Christine Breuil; Nadine Rouard; Florence Deau; Laurent Philippot; Romain L. Barnard (Plant and Soil, 2021)

Seasonal and Interannual Variability of the CO2 System in the Eastern Mediterranean Sea: A Case Study in the North Western Levantine Basin - Cathy Wimart-Rousseau; Thibaut Wagener; Marta Álvarez; Thierry Moutin; Marine Fourrier; Laurent Coppola; Laure Niclas-Chirurgien; Patrick Raimbault; Fabrizio D’Ortenzio; Xavier Durrieu de Madron; Vincent Taillandier; Franck Dumas; et al. (Frontiers in Marine Science, 2021)
The seasonal variability of the carbonate system in the eastern Mediterranean Sea (EMed) was investigated based on discrete total alkalinity (A T ), total dissolved inorganic carbon (C T ), and pH measurements collected during three cruises around Crete between June 2018 and March 2019. This study presents a detailed description of this new carbonate chemistry dataset in the eastern Mediterranean Sea. We show that the North Western Levantine Basin (NWLB) is unique in terms of range of A T variation vs. C T variation in the upper water column over an annual cycle. The reasons for this singularity of the NWLB can be explained by the interplay between strong evaporation and the concomitant consumption of C T by autotrophic processes. The high range of A T variations, combined to temperature changes, has a strong impact on the variability of the seawater p CO 2 ( p CO 2 S W ). Based on Argo float data, an entire annual cycle for p CO 2 S W in the NWLB has been reconstructed in order to estimate the temporal sequence of the potential “source” and “sink” of atmospheric CO 2 . By combining this dataset with previous observations in the NWLB, this study shows a significant ocean acidification and a decrease in the oceanic surface pH T 25 of −0.0024 ± 0.0004 pH T 25 units.a –1 . The changes in the carbonate system are driven by the increase of atmospheric CO 2 but also by unexplained temporal changes in the surface A T content. If we consider that the EMed will, in the future, encounter longer, more intense and warmer summer seasons, this study proposes some perspectives on the carbonate system functioning of the “future” EMed.

Young and mature males have similar energy expenditure during the rut in a trophy-hunted population of Mediterranean mouflon - Gilles Bourgoin; Alice Laurent; Pascal Marchand; Jeanne Duhayer; Marie-Thérèse Poirel; Patricia Michel; Christian Itty; Mathieu Garel (Mammalian Biology, 2021)

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.

Lactosylceramide induced by elastin-derived peptides decreases adipocyte differentiation - Thinhinane Hocine; Sebastien Blaise; Cathy Hachet; Alexandre Guillot; Herve Sartelet; Pascal Maurice; Amar Bennasroune; Laurent Martiny; Laurent Duca; Beatrice Romier-Crouzet; Hassan EL Btaouri (Journal of Physiology and Biochemistry, 2020)

TIMP1 intron 3 retention is a marker of colon cancer progression controlled by hnRNPA1 - Marion Flodrops; Gwendal Dujardin; Adeline Busson; Pascal Trouvé; Chandran Ka; Brigitte Simon; Danielle Arzur; Catherine Le Jossic-Corcos; Laurent Corcos (Molecular Biology Reports, 2020)

A modeling and simulation-based assessment of the impact of confounding factors on the readout of a sildenafil survival trial in pulmonary arterial hypertension - Pascal Chanu; Xiang Gao; Rene Bruno; Laurent Claret; Lutz Harnisch (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Growth Response of Arctica Islandica to North Atlantic Oceanographic Conditions Since 1850 - Pierre Poitevin; Julien Thébault; Valentin Siebert; Sébastien Donnet; Philippe Archambault; Justine Doré; Laurent Chauvaud; Pascal Lazure (Frontiers in Marine Science, 2019)

Coastal Ocean and Nearshore Observation: A French Case Study - Lucie Cocquempot; Christophe Delacourt; Jérôme Paillet; Philippe Riou; Jérôme Aucan; Bruno Castelle; Guillaume Charria; Joachim Claudet; Pascal Conan; Laurent Coppola; Régis Hocdé; Serge Planes; et al. (Frontiers in Marine Science, 2019)

In vivo localization of cortical areas using a 3D computerized atlas of the marmoset brain - Laurent Risser; Amirouche Sadoun; Muriel Mescam; Kuzma Strelnikov; Sandra Lebreton; Samuel Boucher; Pascal Girard; Nathalie Vayssière; Marcello G. P. Rosa; Caroline Fonta (Brain Structure and Function, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Uric acid levels are associated with endothelial dysfunction and severity of coronary atherosclerosis during a first episode of acute coronary syndrome - Mélanie Gaubert; Marion Marlinge; Marine Alessandrini; Marc Laine; Laurent Bonello; Julien Fromonot; Jennifer Cautela; Franck Thuny; Jeremie Barraud; Giovanna Mottola; Pascal Rossi; Emmanuel Fenouillet; et al. (Purinergic Signalling, 2018)

Physiological adjustments and transcriptome reprogramming are involved in the acclimation to salinity gradients in diatoms - Adrien Bussard; Erwan Corre; Cédric Hubas; Evelyne Duvernois‐Berthet; Gildas Le Corguillé; Laurent Jourdren; Fanny Coulpier; Pascal Claquin; Pascal Jean Lopez (Environmental Microbiology, 2017)
Summary Salinity regimes in estuaries and coastal areas vary with river discharge patterns, seawater evaporation, the morphology of the coastal waterways and the dynamics of marine water mixing. Therefore, microalgae have to respond to salinity variations at time scales ranging from daily to annual cycles. Microalgae may also have to adapt to physical alterations that induce the loss of connectivity between habitats and the enclosure of bodies of water. Here, we integrated physiological assays and measurements of morphological plasticity with a functional genomics approach to examine the regulatory changes that occur during the acclimation to salinity in the estuarine diatom Thalassiosira weissflogii . We found that cells exposed to different salinity regimes for a short or long period presented adjustments in their carbon fractions, silicon pools, pigment concentrations and/or photosynthetic parameters. Salinity‐induced alterations in frustule symmetry were observed only in the long‐term (LT) cultures. Whole transcriptome analyses revealed a down‐regulation of nuclear and plastid encoded genes during the LT response and identified only a few regulated genes that were in common between the ST and LT responses. We propose that in diatoms, one strategy for acclimating to salinity gradients and maintaining optimal cellular fitness could be a reduction in the cost of transcription.

Contrasting temporal variation in habitat complexity and species abundance distributions in four kelp forest strata - Jean-Charles Leclerc; Pascal Riera; Laurent Lévêque; Dominique Davoult (Hydrobiologia, 2016)

Lactate recovery kinetics in response to high-intensity exercises - Benjamin Chatel; Carine Bret; Pascal Edouard; Roger Oullion; Hubert Freund; Laurent A. Messonnier (European Journal of Applied Physiology, 2016)

Long-term efficacy and safety of etravirine-containing regimens in a real-life cohort of treatment-experienced HIV-1-infected patients - Clotilde Allavena; Christine Katlama; Laurent Cotte; Pierre Marie Roger; Pierre Delobel; Antoine Cheret; Claudine Duvivier; Isabelle Poizot-Martin; Bruno Hoen; André Cabie; Arnaud Cheret; Rima Lahoulou; et al. (Infectious Diseases, 2016)

Fine and Ultrafine Particles in the Vicinity of Industrial Activities: A Review - Véronique Riffault; Jovanna Arndt; Hélène Marris; Saliou Mbengue; Ari Setyan; Laurent Y. Alleman; Karine Deboudt; Pascal Flament; Patrick Augustin; Hervé Delbarre; John Wenger (Critical Reviews in Environmental Science and Technology, 2015)

Bioaccessibility of trace elements in fine and ultrafine atmospheric particles in an industrial environment - Saliou Mbengue; Laurent Y. Alleman; Pascal Flament (Environmental Geochemistry and Health, 2015)

Calcium signals inhibition sensitizes ovarian carcinoma cells to anti-Bcl-xL strategies through Mcl-1 down-regulation - Marie-Laure Bonnefond; Bernard Lambert; Florence Giffard; Edwige Abeilard; Emilie Brotin; Marie-Hélène Louis; Mor Sény Gueye; Pascal Gauduchon; Laurent Poulain; Monique N’Diaye (Apoptosis, 2015)

A mu–delta opioid receptor brain atlas reveals neuronal co-occurrence in subcortical networks - Eric Erbs; Lauren Faget; Gregory Scherrer; Audrey Matifas; Dominique Filliol; Jean-Luc Vonesch; Marc Koch; Pascal Kessler; Didier Hentsch; Marie-Christine Birling; Manoussos Koutsourakis; Laurent Vasseur; et al. (Brain Structure and Function, 2015)

Molecular evolution and transcriptional regulation of the oilseed rape proline dehydrogenase genes suggest distinct roles of proline catabolism during development - Pascal Faës; Carole Deleu; Abdelkader Aïnouche; Françoise Le Cahérec; Emilie Montes; Vanessa Clouet; Anne-Marie Gouraud; Benjamin Albert; Mathilde Orsel; Gilles Lassalle; Laurent Leport; Alain Bouchereau; et al. (Planta, 2015)

Odor Modification in Salmon Hydrolysates Using the Maillard Reaction - Christelle Kouakou; Jean-Pascal Bergé; Régis Baron; Laurent Lethuaut; Carole Prost; Mireille Cardinal (Journal of Aquatic Food Product Technology, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Impact of climate change on the hydrogeology of two basins in northern France - Florence Habets; Julien Boé; Michel Déqué; Agnès Ducharne; Simon Gascoin; Ali Hachour; Eric Martin; Christian Pagé; Eric Sauquet; Laurent Terray; Dominique Thiéry; Ludovic Oudin; et al. (Climatic Change, 2013)

Divergent evolutionary processes associated with colonization of offshore islands - Natália Martínková; Ross Barnett; Thomas Cucchi; Rahel Struchen; Marine Pascal; Michel Pascal; Martin C. Fischer; Thomas Higham; Selina Brace; Simon Y. W. Ho; Jean‐Pierre Quéré; Paul O'Higgins; et al. (Molecular Ecology, 2013)
Oceanic islands have been a test ground for evolutionary theory, but here, we focus on the possibilities for evolutionary study created by offshore islands. These can be colonized through various means and by a wide range of species, including those with low dispersal capabilities. We use morphology, modern and ancient sequences of cytochrome b ( cytb ) and microsatellite genotypes to examine colonization history and evolutionary change associated with occupation of the O rkney archipelago by the common vole ( M icrotus arvalis ), a species found in continental E urope but not in B ritain. Among possible colonization scenarios, our results are most consistent with human introduction at least 5100 bp (confirmed by radiocarbon dating). We used approximate B ayesian computation of population history to infer the coast of Belgium as the possible source and estimated the evolutionary timescale using a Bayesian coalescent approach. We showed substantial morphological divergence of the island populations, including a size increase presumably driven by selection and reduced microsatellite variation likely reflecting founder events and genetic drift. More surprisingly, our results suggest that a recent and widespread cytb replacement event in the continental source area purged cytb variation there, whereas the ancestral diversity is largely retained in the colonized islands as a genetic ‘ark’. The replacement event in the continental M . arvalis was probably triggered by anthropogenic causes (land‐use change). Our studies illustrate that small offshore islands can act as field laboratories for studying various evolutionary processes over relatively short timescales, informing about the mainland source area as well as the island.

Ensemble reconstruction of the atmospheric column from surface pressure using analogues - Pascal Yiou; Tamara Salameh; Philippe Drobinski; Laurent Menut; Robert Vautard; Mathieu Vrac (Climate Dynamics, 2013)

Nitrogen availability impacts oilseed rape (Brassica napus L.) plant water status and proline production efficiency under water-limited conditions - Benjamin Albert; Françoise Le Cahérec; Marie-Françoise Niogret; Pascal Faes; Jean-Christophe Avice; Laurent Leport; Alain Bouchereau (Planta, 2012)

Folic acid supplementation, MTHFR and MTRR polymorphisms, and the risk of childhood leukemia: the ESCALE study (SFCE) - Alicia Amigou; Jérémie Rudant; Laurent Orsi; Stéphanie Goujon-Bellec; Guy Leverger; André Baruchel; Yves Bertrand; Brigitte Nelken; Geneviève Plat; Gérard Michel; Stéphanie Haouy; Pascal Chastagner; et al. (Cancer Causes & Control, 2012)

Simulation of regional climate change under the IPCC A2 scenario in southeast China - Weilin Chen; Zhihong Jiang; Laurent Li; Pascal Yiou (Climate Dynamics, 2011)

Soil microbial diversity: an ISO standard for soil DNA extraction - Laurent Philippot; Cristina Abbate; Antonio Bispo; Thierry Chesnot; Sara Hallin; Philippe Lemanceau; Kristina Lindström; Pascal Pandard; Esperanza Romero; Michael Schloter; Pascal Simonet; Kornelia Smalla; et al. (Journal of Soils and Sediments, 2010)

The mariner Mos1 transposase produced in tobacco is active in vitro - Xavier Thomas; Sabah Hedhili; Laurent Beuf; Marie-Véronique Demattéi; Hélène Laparra; Giang Ngan Khong; Jean-Christophe Breitler; Frédéric Montandon; Elodie Carnus; Frédéric Norre; Daniel Burtin; Pascal Gantet; et al. (Genetica, 2010)

Genetic diversity and landscape genetic structure of otter (Lutra lutra) populations in Europe - Nadia Mucci; Johanna Arrendal; Hermann Ansorge; Michael Bailey; Michaela Bodner; Miguel Delibes; Ainhoa Ferrando; Pascal Fournier; Christine Fournier; José A. Godoy; Petra Hajkova; Silke Hauer; et al. (Conservation Genetics, 2010)

A benchmark study on problems related to CO2 storage in geologic formations - Holger Class; Anozie Ebigbo; Rainer Helmig; Helge K. Dahle; Jan M. Nordbotten; Michael A. Celia; Pascal Audigane; Melanie Darcis; Jonathan Ennis-King; Yaqing Fan; Bernd Flemisch; Sarah E. Gasda; et al. (Computational Geosciences, 2009)

No limit? The multiphasic uptake of silicic acid by benthic diatoms - Aude Leynaert; Sorcha Ní Longphuirt; Pascal Claquin; Laurent Chauvaud; Olivier Ragueneau (Limnology and Oceanography, 2009)
Silicic‐acid uptake kinetics for a field population of benthic diatoms were examined using a radioisotope tracer over a concentration range of 0‐300 µmol L ‐1 . The microphytobenthos half saturation constant (54 µmol L ‐1 ) and specific uptake rates (0.096 h ‐1 ) for silicic acid were well above those usually found in the pelagic environment. Silicic‐acid kinetics were hyperbolic only at low concentrations (≪60 µmol L ‐1 ). At higher concentrations, a second mechanism that did not suggest saturation was activated. Many benthic diatoms are motile and migrate vertically in the upper few centimeters of sediment where there are strong gradients of nutrient concentrations. The multiphasic uptake may allow them to take maximum advantage of the high silicic‐acid concentrations found at depth.

Transfer of the insecticide [14C] imidacloprid from soil to tomato plants - H. Alsayeda; S. Pascal-Lorber; C. Nallanthigal; L. Debrauwer; F. Laurent (Environmental Chemistry Letters, 2008)

Phytotoxicity to and uptake of TNT by rice - M. Vila; S. Lorber-Pascal; F. Laurent (Environmental Geochemistry and Health, 2008)

Structural and functional analysis of the ovine laminin receptor gene (RPSA): Possible involvement of the LRP/LR protein in scrapie response - Ane Marcos-Carcavilla; Jorge H. Calvo; Carmen González; Carmen Serrano; Katayoun Moazami-Goudarzi; Pascal Laurent; Maud Bertaud; Hélène Hayes; Anne E. Beattie; Jaber Lyahyai; Inmaculada Martín-Burriel; Juan María Torres; et al. (Mammalian Genome, 2008)

Colonization history of the Swiss Rhine basin by the bullhead ( Cottus gobio ): inference under a Bayesian spatially explicit framework - SAMUEL NEUENSCHWANDER; CARLO R. LARGIADÈR; NICOLAS RAY; MATHIAS CURRAT; PASCAL VONLANTHEN; LAURENT EXCOFFIER (Molecular Ecology, 2008)
The present distribution of freshwater fish in the Alpine region has been strongly affected by colonization events occurring after the last glacial maximum (LGM), some 20 000 years ago. We use here a spatially explicit simulation framework to model and better understand their colonization dynamics in the Swiss Rhine basin. This approach is applied to the European bullhead ( Cottus gobio ), which is an ideal model organism to study fish past demographic processes since it has not been managed by humans. The molecular diversity of eight sampled populations is simulated and compared to observed data at six microsatellite loci under an approximate Bayesian computation framework to estimate the parameters of the colonization process. Our demographic estimates fit well with current knowledge about the biology of this species, but they suggest that the Swiss Rhine basin was colonized very recently, after the Younger Dryas some 6600 years ago. We discuss the implication of this result, as well as the strengths and limits of the spatially explicit approach coupled to the approximate Bayesian computation framework.

IL-1 family members as candidate genes modulating scrapie susceptibility in sheep: localization, partial characterization, and expression - Ane Marcos-Carcavilla; Jorge H. Calvo; Carmen González; Katayoun Moazami-Goudarzi; Pascal Laurent; Maud Bertaud; Hélène Hayes; Anne E. Beattie; Carmen Serrano; Jaber Lyahyai; Inmaculada Martín-Burriel; Estefânia Alves; et al. (Mammalian Genome, 2007)

Plate Motion of India and Interseismic Strain in the Nepal Himalaya from GPS and DORIS Measurements - Pierre Bettinelli; Jean-Philippe Avouac; Mireille Flouzat; François Jouanne; Laurent Bollinger; Pascal Willis; Gyani Raja Chitrakar (Journal of Geodesy, 2006)

Fatty acid oxidation and related gene expression in heart depleted of carnitine by mildronate treatment in the rat - Pascal Degrace; Laurent Demizieux; Joseph Gresti; Marcelline Tsoko; Agnès André; Luc Demaison; Pierre Clouet (Molecular and Cellular Biochemistry, 2004)

Mobility of metamorphic fluids inferred from infrared microspectroscopy on natural fluid inclusions: the example of Tinos Island, Greece - Vincent Famin; Satoru Nakashima; Laurent Jolivet; Pascal Philippot (Contributions to Mineralogy and Petrology, 2004)

Recycling plant wax constituents for chemical defense: hemi-biosynthesis of triterpene saponins from ?-amyrin in a leaf beetle - Pascal Laurent; Cedric Dooms; Jean-Claude Braekman; Dsir Daloze; Jean-Louis Habib-Jiwan; Raoul Rozenberg; Arnaud Termonia; Jacques M. Pasteels (The Science of Nature, 2003)

Occupational risk factors, ultraviolet radiation, and ocular melanoma: a case–control study in France - Pascal Guénel; Laurent Laforest; Diane Cyr; Joëlle Févotte; Svend Sabroe; Cécile Dufour; Jean-Michel Lutz; Elsebeth Lynge (Cancer Causes & Control, 2001)

Assignment of 60 human ESTs in cattle - Pascal Laurent; Carmen Elduque; Hélène Hayes; Katyana Saunier; André Eggen; Hubert Levéziel (Mammalian Genome, 2000)

Simultaneous observations of tuna movements and their prey by sonic tracking and acoustic surveys - Erwan Josse; Pascal Bach; Laurent Dagorn (Hydrobiologia, 1998)